2011
DOI: 10.1007/s00296-011-1861-7
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular nodular fasciitis of the knee: a rare cause of recurrent hemarthrosis

Abstract: A 20-year-old man presented with pain and recurrent hemarthrosis in the right knee. Magnetic resonance imaging of the knee showed a lesion with homogeneous low signal intensity on T1-weighted images and a heterogeneous, low to high signal intensity on T2-weighted images. At arthroscopy, the mass was located between the posterior cruciate ligament and the posterior knee joint capsule. The tumor was excised through a posterior approach and histologically diagnosed as a nodular fasciitis. Intra-articular nodular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 8 publications
3
11
0
Order By: Relevance
“…There were no morphologic differences seen in the lesions based on the location, as previously described. In addition, there was no intra‐osseous or intra‐articular extension of the lesions, as described in other publications 11 , 16 18 …”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…There were no morphologic differences seen in the lesions based on the location, as previously described. In addition, there was no intra‐osseous or intra‐articular extension of the lesions, as described in other publications 11 , 16 18 …”
Section: Discussionsupporting
confidence: 75%
“…Sonograms were acquired with high-frequency linear array (12)(13)(14)(15)(16)(17) MHz) transducers on clinical ultrasound machines (LOGIQ 9; GE Healthcare, Wauwatosa, WI; and HDI 5000 and iU22; Philips Healthcare, Bothell, WA) as part of routine patient care. Magnetic resonance images were acquired on a clinical 1.5-T system (Signa Excite; GE Healthcare).…”
Section: Imagingmentioning
confidence: 99%
“…Although information on imaging studies for intra-articular nodular fasciitis is limited, the current case showed nonspecific findings on MRI images, with homogeneous iso to low signal intensity on T1-weighted images and a heterogeneous, low to high signal intensity on T2-weighted images as reported previously (3)(4)(5)(6)(7). In this present case, conventional MRI with no contrast study showed nonspecific signal intensity of the lesion similar to previous reports, resulting in difficulty in making a precise pre-operative diagnosis on MRI.…”
Section: Index Termsmentioning
confidence: 81%
“…Nodular fasciitis is a benign, subcutaneous tumor‐like lesion caused by myofibroblastic proliferation, and is usually found on the upper limbs, trunk, head, and neck [1–3]. Intra‐articular nodular fasciitis is rarely reported.…”
mentioning
confidence: 99%
“…Intra‐articular nodular fasciitis is rarely reported. It is difficult for clinicians to differentiate nodular fasciitis from other tumor‐like lesions solely by imaging [3]. Because of the possibility of malignancy, such as malignant fibrous histiocytoma [2], surgical exploration is required for confirmation of pathology.…”
mentioning
confidence: 99%